Exploring the potential of olive pomace derived activated charcoal as an efficient adsorbent for methylene blue dye: a comprehensive investigation of isotherms, kinetics, and thermodynamics - Imad Alouiz; Mohssine Benhadj; Elmontassir Dahmane; Abdeslam Mouadili; Mohamed Sennoune; Mohamed Yassine Amarouch; Driss Mazouzi (Materials Research Express, 2024)
Methylene blue (MB) is a heterocyclic aromatic chemical compound used as a dye in various dyeing processes. The accumulation of such an organic compound poses a significant threat to both the environment and human health. Therefore, numerous biological, physical, and chemical processes have been established to remove MB dye, with adsorption being the most predominant dye-based treatment technology. In this context, the aim of this work was to evaluate the adsorption properties of activated carbon derived from olive pomace against methylene blue. To this end, scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy (EDS), and Fourier transform infrared spectroscopy (FT-IR) analyses were carried out to confirm the adsorption of MB on carbon structures. In addition, the effect of contact time, pH, initial dye concentration, adsorbent dose, and temperature on the adsorption efficiency of MB was investigated. On the other hand, kinetic and isothermal models were used to further understand the adsorption mechanism, which showed a good correlation with the pseudo-second-order kinetic model and the Langmuir isotherm. Finally, thermodynamic analysis showed favorable conditions for physisorption, with the process being both endothermic and spontaneous.